Gambaran Kelengkapan Berkas Rekam Medis Pasien Rawat Inap Kasus Bedah di RSU ‘Aisyiyah Padang - Siska, Siska; Wahyuni, Annisa; Oktavia, Dewi (Indonesian of Health Information Management Journal (INOHIM), 2024)
Abstract                                                                          Based on the Minimum Service Standards for Hospitals, one of the indicators of medical record services is the completeness of medical record documents, which should be 100%. To improve the quality of services, a qualitative analysis is needed to identify deficiencies in documentation. This study aims to provide an overview of the completeness of inpatient surgical case medical records based on a qualitative review at RSU 'Aisyiyah Padang in 2023. The research method used is descriptive quantitative. The population of this study consists of medical record documents from 2023. The sampling technique used is simple random sampling with a total of 90 documents. The results show that the review of the completeness and consistency of diagnoses was 87.0% complete and 13.0% incomplete. The review of diagnosis recording consistency showed 92.6% complete and 7.4% incomplete. The review of actions taken during treatment and medication showed 82.2% complete and 17.8% incomplete. The review of informed consent completeness showed 82.2% complete and 17.8% incomplete. The review of recording practices showed 73.3% complete and 26.7% incomplete. The study suggests that the hospital should implement policies regarding sanctions for medical personnel who do not complete medical records and establish SOPs for evaluating and monitoring the completeness of medical records. Keyword: completeness, consistency, recording, medical records, treatment AbstrakBerdasarkan Standar Pelayanan Minimal Rumah Sakit, salah satu indikator pelayanan rekam medis adalah kelengkapan dokumen rekam medis sebesar 100%. Untuk meningkatkan standar mutu pelayanan, diperlukan analisis kualitatif guna mengidentifikasi kekurangan dalam pencatatan. Penelitian ini bertujuan untuk mengetahui gambaran kelengkapan berkas rekam medis rawat inap kasus bedah berdasarkan review kualitatif di RSU 'Aisyiyah Padang tahun 2023. Metode penelitian yang digunakan adalah kuantitatif deskriptif. Populasi penelitian ini adalah berkas rekam medis tahun 2023. Teknik pengambilan sampel menggunakan simple random sampling dengan jumlah 90 dokumen. Hasil penelitian menunjukkan bahwa review kelengkapan dan kekonsistensian diagnosis didapatkan 87,0% lengkap dan 13,0% tidak lengkap. Review kekonsistensian pencatatan diagnosis menunjukkan 92,6% lengkap dan 7,4% tidak lengkap. Review hal-hal yang dilakukan saat perawatan dan pengobatan menunjukkan 82,2% lengkap dan 17,8% tidak lengkap. Review kelengkapan informed consent menunjukkan 82,2% lengkap dan 17,8% tidak lengkap. Review cara atau praktik pencatatan menunjukkan 73,3% lengkap dan 26,7% tidak lengkap. Penelitian ini menyarankan agar rumah sakit membuat kebijakan mengenai sanksi untuk pendisiplinan tenaga medis yang tidak melengkapi rekam medis dan membuat SOP mengenai evaluasi dan pengawasan kelengkapan rekam medis.Kata Kunci: kelengkapan, konsistensi, pencatatan, perawatan, rekam medis